Mekanisme Adaptasi Genotipe Baru Kedelai dalam Mendapatkan Hara Fosfor dari Tanah Mineral Masam - Rr. Yudhy Harini Bertham; Abimanyu Dipo Nusantara (Indonesia Society of Agronomy (PERAGI) and Department of Agronomy and Horticulture, Faculty of Agriculture, IPB University, Bogor, Indonesia, 2011)
Phosphate defi ciency is one of the main constraints to increase soybean yield in acid mineral soil. An experiment was conducted with an objective to discover scientifi c base of fertilizer selection based on soybean adaptation mechanism to mitigate P defi ciency in acid mineral soils in Bengkulu Province. A factorial experiment was arranged in a randomized complete block design with four replications. The fi rst factor was soybean genotypes, i.e. Slamet and three new soybean genotypes (NSGs) i.e. 19BE, 25EC and 13ED, and second factor was P fertilization dosages (0 and 400 mg P2O5 kg-1 soil). Soybean was grown in a greenhouse using double pot system. Research results showed that the NSGs had different mechanism in P uptake from soil with high P absorbing capacity compared to Slamet genotype. NSGs translocated more carbon to root, and decreasing of shoot-root ratio, about 66-70%. NSGs 25EC produce more oxalic and malic acid, and 13ED produce more citric acid to obtain same amount of P absorbed by Slamet variety. Under low P, NSGs developed symbioses with mycorrhizal arbuscular fungus, however, only 19BE which increase microbe population in rhizosfer. Phosphosrus fertilization supressed arbuscular mycorrhizal fungus development (15-100%), alkaline phosphatase activity (20-88%), and microbial C biomass (40-71%) in rhizosphere of new soybean genotypes